The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1590/pboci.2021.081
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude About Research Ethics Among Iranian Dental Students

Abstract: Objective: To evaluate the knowledge and attitude of the students of Kerman dental school (Iran) about ethics in dental research. Material and Methods: This cross-section study was conducted on 307 dental students selected through the census sampling method. Data were collected by a researcher-made questionnaire consisting of 12 items about knowledge and 17 items about attitude toward research ethics. Data analyzed in SPSS software using t-test and linear regression test. P-values of less than 0.05 were consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Considering the involvement of general scarcity of information in this regard, especially in the dental field in Iran, and in continuing our interest in medical research [24][25][26][27] and most of the published articles on occupational hazards are in nurses and articles related to occupational hazards in dentists are based on skeletal problems and burnout. Therefore, as there are no studies on occupational hazards of dentists in Kerman covering most of occupational hazards and evaluating the awareness of occupational hazards can help identify the most common problems of dentists, this study was conducted to examine the frequency of occupational hazards in general dentists in Kerman (South East of Iran).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the involvement of general scarcity of information in this regard, especially in the dental field in Iran, and in continuing our interest in medical research [24][25][26][27] and most of the published articles on occupational hazards are in nurses and articles related to occupational hazards in dentists are based on skeletal problems and burnout. Therefore, as there are no studies on occupational hazards of dentists in Kerman covering most of occupational hazards and evaluating the awareness of occupational hazards can help identify the most common problems of dentists, this study was conducted to examine the frequency of occupational hazards in general dentists in Kerman (South East of Iran).…”
Section: Introductionmentioning
confidence: 99%
“…Attitudes toward research ethics and RECs did not differ significantly across Myanmarese post-graduate medical students with and without prior research ethics training (Than et al, 2020). Torabi et al (2021), on the contrary, found that completion of a research ethics workshop was a significant predictor of dental students’ attitudes to research ethics principles in Iran. Iranian dental students who previously attended medical research ethics workshops were more likely to have positive attitudes toward research ethics principles compared to students who did not attend such workshops.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies that examined issues of implementing ethical regulations in research involving humans in developing research contexts (Azakir et al, 2020; El-Dessouky et al, 2011; Kandeel et al, 2011; Than et al, 2020; Torabi et al, 2021) also explored associations between researchers’ awareness of and attitudes toward research ethics and RECs and a number of baseline demographic and socio-economic characteristics (e.g. gender, prior research ethics training, research experience).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this finding, Janakiram & Gardens (2014) demonstrated that sex was not associated with participants' knowledge about ethics. In a study conducted by Torabi et al (2021), females displayed a higher mean knowledge score (7.69) than males (7.03) but the difference was not significant (p = 0.077). Moreover, Tarboush et al (2020) did not detect any significant association between correct answers about the DH and the participants' sex.…”
Section: Association Between Sex Years Of Experience and Participants...mentioning
confidence: 82%